2020
DOI: 10.21608/javs.2020.100157
|View full text |Cite
|
Sign up to set email alerts
|

Review On Some Heavy Metals Toxicity On Freshwater Fishes

Abstract: Heavy metals contamination is a serious problem in the aquatic environment. Some of them are very important, having biological roles for aquatic organisms, and called essential heavy metals. In contrast, other heavy metals are considered harmful even at low concentrations. The toxic levels of heavy metals may be of agricultural, industrial and mining activities. This will cause water pollution and changes in the physicochemical characteristics of the aquatic environment. This pollution has deleterious toxic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…In rodents, bone concentration of Al >10 μg.g -1 has been considered to indicate a reduction in the ability of the animal to excrete Al or an indication of exposure to high concentrations of Al (Scheuhammer 1987). Aluminium is known to be toxic to invertebrates and freshwater shes (van Dam et al 2018, AL-Taee et al 2020, neurotoxic to humans as well as causing disturbances in cellular growth, communication and secretory functions, and reductions in bone tissue (Barabasz et al 2002). There is concern that important metabolic processes in birds and mammals could be negatively affected by Al uptake in environments containing high concentrations of Al (Rosseland et al 1990) since Al has been shown to negatively affect phosphorous (P) and Ca metabolism resulting in bone abnormalities, weakness of muscle and decreased growth rates (Scheuhammer 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, bone concentration of Al >10 μg.g -1 has been considered to indicate a reduction in the ability of the animal to excrete Al or an indication of exposure to high concentrations of Al (Scheuhammer 1987). Aluminium is known to be toxic to invertebrates and freshwater shes (van Dam et al 2018, AL-Taee et al 2020, neurotoxic to humans as well as causing disturbances in cellular growth, communication and secretory functions, and reductions in bone tissue (Barabasz et al 2002). There is concern that important metabolic processes in birds and mammals could be negatively affected by Al uptake in environments containing high concentrations of Al (Rosseland et al 1990) since Al has been shown to negatively affect phosphorous (P) and Ca metabolism resulting in bone abnormalities, weakness of muscle and decreased growth rates (Scheuhammer 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In the lowest sub-lethal concentrations of metals and pesticides, the fish survival was between 97.5% and 100%, hence these concentrations were found to be suitable for survival test. 50,51,52 Acute and Chronic Safe Concentrations Analogous to the acute safe level, the chronic safe values were also derived using the NOEC and LOEC values obtained through survival studies.…”
Section: Chronic Toxicitymentioning
confidence: 99%
“…It can also accumulate in the thyroid and increase the risk of autoimmune disorders [30] In Tanzania, most of our local feed ingredients are multipurpose and used in the formulation of different animal feeds like pig feeds, poultry pellets, cattle feed and fish pellets. When taking up the feed, animals may also take some concentrations of heavy metals, transitional metals and end up metabolizing, excreting, storing or bio-accumulating them in the body [31]. Therefore, it is important for the feed ingredients to comply with the maximum limits of heavy and other toxic metals established by various regulatory authorities in the world and the present study aims to assess the concentration of transitional and toxic heavy metals in the commonly used feed ingredients for Nile tilapia (Oreochromis niloticus) diets obtained from northern part of Tanzania and ensure that fish feeds are not contaminated with toxic metals or do not exceed their maximum permissible limits.…”
Section: Introductionmentioning
confidence: 99%